Tourism and Changing Pattern of Livelihood - Prasai, Dilli R (Researcher: A Research Journal of Culture and Society, 2014)
Barahachhatra have got good food, shelter, entertainment, education and others through tourism and they have got standard life and tourism industry is being own of the great for them to change their lifestyle positively.Tourism industry is the employment generating industry in the context of our country. It gives employment for skilled and unskilled people. The employment opportunity has significantly increased in Barahachhatra with the development of tourism business especially by hotel industries and then hotel owner and employees have positively changed their lifestyle by the help of tourism. DOI: http://dx.doi.org/10.3126/researcher.v1i2.9883 Researcher 1(2) 2013: 23-34